The Effects of Attraction, Promotion and Accessibility on Revisiting Intention to Tana Toraja, South Sulawesi, Indonesia - Isdar Wahim; Jui-Yuan Chu; Thao-Trang Huynh-Cam (Politeknik Pariwisata Lombok, 2023)
This study aims to determine the effect of attraction, promotion, and accessibility on revisiting intention to Tana Toraja, a mountainous region in South Sulawesi Province, Indonesia. The data was obtained from a total of 357 respondents who were domestic tourists and chosen randomly to answer a questionnaire in various public places. Regression analysis showed that the attraction, promotion, and accessibility have positive effects on tourists’ revisit intention to Tana Toraja, South Sulawesi, Indonesia. The output from the objective variable analysis can have good implications for the increase in tourist visits to Toraja in the current pandemic situation. From the samples collected, it was found that the average tourist who had visited Tana Toraja was 4.65, which means that these tourists have a strong intention to return to visit.